Retirement planning : The preparation of Uda Land (South) Sdn. Bhd. staff / Muhammad Khairul Anwar - Anwar, Muhammad Khairul (Faculty of Administrative Science and Policy Studies, 2013)
Retirement planning is ever more important in the world today and more so in the future. The increase in the cost of living and economic uncertainties have make it more pressing for people to be more prepared for their retirement. This study is conducted to find out the staffs of the UDA Land (South) Sdn Bhd preparation towards retirement. This research explores their retirement preparedness and perceptions of retirement and retirement planning. By taking part in this study, it result to a better view for all students to know the utmost importance to plan and prepares for their retirement days later on in the future. In the research, the data are collected from 150 selected staffs UDA Land employees via questionnaire as well as interview. The questionnaires were distributed to all the staffs, and they responded well and showing cooperation in helping to produce such accurate and reliable data.